Revealing the Yeast Diversity of the Flor Biofilm Microbiota in Sherry Wines Through Internal Transcribed Spacer-Metabarcoding and Matrix-Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry - Carbonero-Pacheco, Juan; Moreno-García, Jaime; Moreno, Juan; García-Martínez, Teresa; Mauricio, Juan Carlos (Frontiers in Microbiology, 2022)
Flor yeast velum is a biofilm formed by certain yeast strains that distinguishes biologically aged wines such as Sherry wine from southern Spain from others. Although Saccharomyces cerevisiae is the most common strain, 5.8 S-ITS restriction fragment length polymorphism (RFLP) analyses have revealed the existence of non-Saccharomyces species. In order to uncover the flor microbiota diversity at a species level, we used next-generation sequencing (NGS) and matrix-assisted laser desorption time of flight mass spectrometry (MALDI-TOF MS) techniques. Further, to enhance identification effectiveness, we performed an additional incubation stage in 1:1 wine:YPD before identification. Six species were identified: Saccharomyces cerevisiae, Pichia manshurica, Pichia membranifaciens, Wickerhamomyces anomalus, Candida guillermondii, and Trichosporon asahii, two of which were discovered for the first time (C. guillermondii and T. ashaii) in Sherry wines. We analyzed wines where non-Saccharomyces yeasts were present or absent to see any potential link between the microbiota and the chemical profile. Only two significant volatile chemicals (out of 13 quantified), ethanol and ethyl lactate, and two enological parameters (out of 6 quantified), such as pH and titratable acidity, were found to differ in long-aged wines. Although results show a low impact where the non-Saccharomyces yeasts are present, these yeast isolated from harsh environments (high ethanol and low nutrient availability) could have a potential industrial interest in fields such as food microbiology and biofuels production.